2021
DOI: 10.1016/j.cytox.2021.100058
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive inhibition of IL-6 trans-signaling by soluble gp130FlyRFc

Abstract: Highlights A variety of sgp130Fc muteins was generated. Introduction of a gp130 SNP (R281Q) into sgp130Fc increases IL-6 specificity. The sgp130Fc variant sgp130 FlyR exclusively affects IL-6 trans-signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Similarly, IL-6 was selected as a representative anti-inflammatory target for molecular docking in this study because of its importance in inflammation. Site I in IL-6 is the binding domain of IL-6R and is closely associated with classic signaling pathways [ 21 , 22 ]. Therefore, a grid box (126 Å × 126 Å × 114 Å, 0.375 Å spacing) was constructed around site I and centered at the following coordinates: x = 1.301, y = −19.932, z = 8.838.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, IL-6 was selected as a representative anti-inflammatory target for molecular docking in this study because of its importance in inflammation. Site I in IL-6 is the binding domain of IL-6R and is closely associated with classic signaling pathways [ 21 , 22 ]. Therefore, a grid box (126 Å × 126 Å × 114 Å, 0.375 Å spacing) was constructed around site I and centered at the following coordinates: x = 1.301, y = −19.932, z = 8.838.…”
Section: Resultsmentioning
confidence: 99%
“…The studies by Gross et al demonstrated that serum concentrations of IL6 in patients with in ammatory bowel disease, as compared to healthy controls, increased signi cantly [30] . Further study found that high expression of IL6 was common in patients with Crohn's disease and ulcerative colitis and closely associated with disease activities [31] . Louis et al have used high IL6 serum levels as the biomarkers to predict for stopping recurrence in patients with Crohn's disease [32,33] .…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Gross et al demonstrated that serum concentrations of IL6 in patients with inflammatory bowel disease, compared to healthy controls, increased significantly [ 30 ]. Further study found that high expression of IL6 was common in patients with Crohn's disease and ulcerative colitis and was closely associated with disease activities [ 31 ]. Louis et al used high IL6 serum levels as biomarkers to predict recurrence cessation in patients with Crohn’s disease [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%